Self-esteem, emotional intelligence, alcohol consumption, tobacco, social support and academic performance in nursing students - Pérez Briones, Nancy Griselda; Muñoz Morales, Alejandra; Covarrubias Solís, Irma Fabiola; Villa Rivas, Fani; Castillo Díaz, Rocio (Horizonte Sanitario, 2025)
Objetive: Identify the relationship that exists between self-esteem, emotional intelligence, alcohol consumption, tobacco, social support and academic performance in nursing students. Material and methods: Descriptive, cross-sectional and correlational study. The sample was 694 undergraduate nursing students from northern and central Mexico. The instruments used were sociodemographic Data Card, Rosenberg Self-Esteem Sale, Trait Meta Mood Scale-24, CAGE Instrument, Fagestrom Test, Family and Friends Social Support Scale. Results: 80.4% were women, 56.9% reported high self-esteem; 49.3% reported high emotional intelligence, 48.6% consumed alcohol and 17.7% tobacco; 54.6% always have social support. Self-esteem is positively and significantly related to emotional intelligence ((rs= .223, p<.05), negatively and significantly related to alcohol consumption (rs= -.136, p<.05); positive and significant with social support (rs= .403, p<.05). The relationship of self-esteem with the different variables is significant (f = 5.930, p >.001) and is explainded by 21.5% with social support and academic performance being predictive factors. Conclusion: A positive and significant relationship is shown between self-esteem, emotional intelligence and social support. And a negative and significant relationship between self-esteem and alcohol consumption. The present results show the relevance of implementing prevention and support programs for nursing students during their university studies. The present results show the relevance of implementing prevention and support programs for nursing students during their university studies. Keywords: Self Concept; Alcoholism; Tobacco Use Disorder; Social Support; Academic Performance.